Response of Eggplant, Yard-Long Bean, and Kangkong on Polyethylene Mulched and Drip Irrigation System - Anas Dinurrohman Susila; Angga Agung Gumelar (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Eggplant, yard long bean, and kangkong, were grown with polyethylene mulch with a drip irrigation system on Podzolic soil with low pH (4.5), low C-Organic (0.97%), very low total-N (0.17 %), low K content (0.15 me (100 g)-1), but had a high soil P2O5 concentration (13.7 ppm) to evaluate the best crop management practices under this soil condition. Combination of polyethylene mulch treatments (with and without), fertilizer (with and without), number of irrigation lines (0, 1, and 2 lines), and methods of fertilizer applications (preplant, split, and drip) were arranged in a Randomized Completely Block Design with four replications. The results showed that the use of mulch and fertilizer signiﬁ cantly increased yield of all crops. One line irrigation system also resulted in the best yield. Preplanting application of 100% P, 50% N and K in addition to 50% N and K applied 10 times weekly was the best methods to produce Eggplant, Yard Long Bean, Kangkong under polyethylene mulched and drip irrigation system. Keywords: Solanum melongena L, fertilization, fertigation, Ipomoea reptans L, micro-irrigation, polyethylene-mulched, Vigna unguilata L.